ANALISIS PENDEKATAN TaRL DALAM PENINGKATAN KEMAMPUAN LITERASI MEMBACA SISWA KELAS III DI MIS TANGGA - Rahmi Ulfa; Syarifudin; Syarifuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of the Teaching at the Right Level (TaRL) approach in improving reading literacy skills of third-grade students at MIS Tangga. The TaRL approach emphasizes instruction tailored to students' actual learning levels rather than their grade level. This descriptive qualitative research employed data collection techniques such as observation, interviews, documentation, and questionnaires. The results showed that most students responded very positively to the implementation of TaRL, with several questionnaire statements rated in the